Penggambaran Peran Gender dalam Keluarga di Film Noktah Merah Perkawinan - Justin Rain Marajo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine the depiction of gender roles in the 2022 film version of Noktah Merah Perkawinan, which is a remake of the 1996 television series. The focus of the film is the dynamics of the marriage of a couple who have been married for 11 years. This research employs a qualitative approach with text analysis methods. The analysis technique used is Roland Barthes' semiotic analysis technique which consists of three stages, namely denotation, connotation, and myth. Meanwhile, the theory used in this research is symbolic interactionalism theory which emphasizes the concepts of roles and values. The data used include documentation of film scenes that meet the predetermined analysis criteria as well as related published journals. The results show that the depiction of gender roles in this film is still not ideal. Although both men and women are portrayed in domestic and public roles, domestic roles are predominantly held by women. This is due to the persistent traditional stereotypes, where women are seen as responsible for the domestic sector, while men are encouraged to take responsibility in the public sector. In conclusion, this film still maintains traditional stereotypes in the depiction of gender role distribution.